Integração e interdisciplinaridade no processo ensino/aprendizagem de projeto: o curso de Arquitetura e Urbanismo da Universidade Potiguar de Mossoró-RN - Jácome, Maria de Fátima Torres (2016)
Training in Architecture and Urbanism with its general characteristic involves, in its nature, knowledge of various areas (technology, theory, history, representation, and design), being the space of design conception that place where the synthesis of this knowledge is reflected more clearly. We believe that the integrated work in the architectural curriculum can provide an overview of the project, thus contributing to better training of the architect. This research aims to reflect on the role of integration and interdisciplinary in teaching architectural design. This theme has been work recurrently by critics in the teaching area of project and events of the area as the seminars of the Projetar, highlighted by several authors to search integration as an essential pedagogical approach to design education. The work aims to contribute to reflection and awareness of those involved on the importance of integration in the architectural course of project processes. For this, we analyzed the potential and limits of this process in Architecture and Urbanism Course (CAU) at the Universidade Potiguar (UNP) Mossoró, which has the integration and interdisciplinary recorded since the Pedagogical Project of the Course. This analysis will be performed by observing the development of “interdisciplinary work” in the fifth term during the first half of 2014.1. This research concerns an exploratory qualitative study that aims to investigate specific issues on the teaching/learning architecture project and the integration in architecture courses, following a non-participant observation in architectural design classes in the fifth term of CAU/UnP/ Mossoró, and analysis of final products, which would be the work of the last unit of the semester, called “Interdisciplinary work”. Questionnaires for the teachers who participated in the process has been apply via email and analyzed. Reflection supports several other already carried out to identify the difficulties inherent in applying these principles satisfactorily. Noting, however, that interdisciplinarity, in fact, it goes beyond integration and is even more difficult to achieve. In addition to an educational project that incorporates these principles, such as the course of Architecture and Urbanism of the UNP-Mossoró, full adhesion it is necessary by the faculty and students of this teaching philosophy.